Area-level socioeconomic inequalities in hypertension care cascade in China: a nationwide population-based study based on the ChinaHEART projectResearch in context - Wenyao Peng; Siqi Lin; Xuan Liu; Bowang Chen; Xueke Bai; Chaoqun Wu; Xiaoyan Zhang; Yang Yang; Jianlan Cui; Wei Xu; Lijuan Song; Hao Yang; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Socioeconomic status (SES) is one of key social determinants of health. Compared to individual-level SES, the association between area-level SES and hypertension management has been understudied and under-recognised. In this study, we aimed to assess the association between area-level SES and hypertension awareness, treatment, combination therapy and control, and the modification effect of individual characteristics on the associations. Methods: During Dec 2015 and Dec 2022, 1,559,748 residents with hypertension aged 35–75 years from 31 provinces in the China Health Evaluation And risk Reduction through nationwide Teamwork (ChinaHEART) were included. The composite value of area-level SES was generated from national census data and categorized into tertiles. Multivariable mixed models with random effects to account for county-level administrative area were fitted to compute odds ratios (OR) and 95% confidence intervals (CIs) for the independent and interactive associations of both area- and individual-level SES with hypertension management (awareness, treatment, combination therapy and control) and their disparities across different population subgroups. Findings: Among the included participants with hypertension aged 59·1 ± 9·1 years, 794,675 (50·95%), 650,485 (41·70%) and 206,103 (13·21%) were aware, treated, and controlled, respectively. Compared with the high area-level SES group, the low group was significantly associated with a lower odds of hypertension awareness (OR: 0·75, 95% CI: 0·65–0·86), treatment (0·69, 0·59–0·81), combination therapy (0·65, 0·51–0·84), and control (0·62, 0·51–0·75). Participants with low SES at both individual and area level had the lowest odds of hypertension management. Area-level SES had stronger influences on hypertension awareness, treatment and control, but a weaker influence on combination therapy, in the young and those with high individual-level SES. Interpretation: Area-level SES on plays a key role in the awareness, treatment, combination therapy and control of hypertension, with different magnitude of associations. Integrated action to improve area-level circumstances and promote targeted interventions to hypertension care cascade are needed to reduce health inequalities in China. Funding: The CAMS Innovation Fund for Medical Science; the National High Level Hospital Clinical Research Funding; the National Natural Science Foundation of China of China; the Ministry of Finance of China and National Health Commission of China; the 111 Project from the Ministry of Education of China.